A qualitative systematic review protocol for a synthesis of teachers’ and learners’ experiences with the Teaching and Learning Toolkit - Kantor, Jiri; Smrckova, Alzbeta; Zaman, Mohammad; Belkin, Liliana; Rozmarinova, Jana; Svobodova, Zuzana; Sedlackova, Dagmar; Klugarova, Jitka (Frontiers in Education, 2025)
The best available evidence on educational strategies should inform the decision-making of teachers, policy-makers, and other stakeholders in the field of education. The Teaching and Learning Toolkit created by the UK-based Education Endowment Foundation (EEF Toolkit) is recognized as one of the most important tools providing information on effectiveness, costs, and certainty of evidence for 30 education strategies. However, the latest version of the EEF Toolkit from 2021 does not provide information on users’ experience with the strategies. Therefore, we selected the 10 most effective strategies and designed a protocol for a qualitative systematic review to summarize the experiences of teachers/learners (aged 3–18 years) with these selected strategies in the context of schooling. All stages of this systematic review will be conducted and reported in line with JBI methodology and PRISMA 2020 statement. The search will be carried out in following information sources: APA PsycINFO (EBSCOhost), PubMed (NLM), ERIC (EBSCOhost), SocINDEX with Full Text (EBSCOhost), Academic Search Ultimate (EBSCOhost), Web of Science Core Collection (Clarivate Analytics), Scopus (Elsevier), ProQuest Central (ProQuest), OpenDissertations (EBSCOhost), ProQuest & Dissertation Theses (Clarivate Analytics), and Google Scholar (Google). The selection of relevant studies, critical appraisal, data extraction and synthesis will be conducted by two independent reviewers. The ConQual approach will be used to assess the certainty of evidence of all synthetized findings.